2014
DOI: 10.3324/haematol.2014.110742
|View full text |Cite
|
Sign up to set email alerts
|

Focused chemical genomics using zebrafish xenotransplantation as a pre-clinical therapeutic platform for T-cell acute lymphoblastic leukemia

Abstract: transplantation (XT) can support the use of patient diagnostic biopsy material, but are better suited to moderate throughput drug-screening than mice. 16,17 Relatively low maintenance costs and short time intervals to complete in vivo studies, as well as their size and transparency that facilitate analyses, make the zebrafish an attractive model for the screening of anti-cancer agents.18 Specifically, zebrafish XT has gained considerable attention as a system to rapidly study and directly observe tumor cell be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 37 publications
0
78
1
Order By: Relevance
“…Whilst this can be achieved post-mortem by detecting human-specific antigens using immunocytochemistry ( Bentley et al , 2015), the use of lipophilic fluorescent cell membrane stains in conjunction with zebrafish transgenic lines allows much more data to be collected from animals of greater immaturity. However, quantification of xenografted cancer cell proliferation is equivalent when measured using either membrane stains or fluorescent proteins ( Bentley et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Whilst this can be achieved post-mortem by detecting human-specific antigens using immunocytochemistry ( Bentley et al , 2015), the use of lipophilic fluorescent cell membrane stains in conjunction with zebrafish transgenic lines allows much more data to be collected from animals of greater immaturity. However, quantification of xenografted cancer cell proliferation is equivalent when measured using either membrane stains or fluorescent proteins ( Bentley et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Transplanting malignant patient tissue or cells into hundreds of zebrafish embryos and monitoring the response to planned investigational drug treatments could yield valuable information on the most suitable drug to be administered for that particular patient. Evidence of a response to a small-molecule inhibitor might indicate effective targeting of an actionable genetic driver lesion, as we observed for a child with T-ALL who expressed a novel γ-secretase-responsive Notch mutation (Bentley et al, 2013) (V. L. Bentley, C.J.V., D. P. Corkery, J. B. Pinder, M. A. LeBlanc, K. Bedard et al, unpublished results).…”
Section: Clinical Applications Of the Zebrafish Xenotransplantation Pmentioning
confidence: 52%
“…The absence of certain genes in the zebrafish can also be exploited as a means of identifying human xenografted cells from the zebrafish embryo in ex vivo analyses and immunohistochemistry. For example, we have recently used the promyelocytic leukemia (PML) protein, for which the gene is absent in the zebrafish, as a marker of human primary T-cell leukemia cells during ex vivo proliferation analyses (Bentley et al, 2013). Finally, it should be noted that the human tumor xenografts interact with, and in many instances remodel, the host tissue following engraftment; for example, host vasculature can be recruited by tumor xenografts (Zhao et al, 2011).…”
Section: Zebrafish Xenotransplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since much less human material is required to generate a xenograft, establishing zPDXs using tumor biopsy samples can be more feasible than in mice. To the best of our knowledge, at least two studies already reported the generation of zPDX with biopsy samples [118,127]. Importantly, there is no need for cell culture amplification [105,106,118], thus reducing the time and number of artefactual steps required for in vitro adaptation.…”
Section: Advantages Of the Zebrafish Larval Xenograft Modelmentioning
confidence: 99%